2019
DOI: 10.1109/tvt.2019.2910217
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Reputation Management Schemes of Internet of Vehicles Based on Evolutionary Game Theory

Abstract: Conducting reputation management is very important for Internet of vehicles. However, most of the existing researches evaluate the effectiveness of their schemes with settled attacking behaviors in their simulation which cannot represent the scenarios in reality. In this paper, we propose to consider dynamical and diversity attacking strategies in the simulation of reputation management scheme evaluation. To that end, we apply evolutionary game theory to model the evolution process of malicious users' attackin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 168 publications
(86 citation statements)
references
References 46 publications
(35 reference statements)
0
77
0
Order By: Relevance
“…In addition, this article studies a variety of stability enhancement methods for reverse TCP connection sessions. 17 This study is valid for most Android systems 23 and contributes greatly to improving the quality of penetration testing. In the future, we will continue to follow up on the security improvements of the Android operating system, propose more effective analysis methods, and find and propose feasible solutions to protect the security of mobile intelligent terminals.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…In addition, this article studies a variety of stability enhancement methods for reverse TCP connection sessions. 17 This study is valid for most Android systems 23 and contributes greatly to improving the quality of penetration testing. In the future, we will continue to follow up on the security improvements of the Android operating system, propose more effective analysis methods, and find and propose feasible solutions to protect the security of mobile intelligent terminals.…”
Section: Resultsmentioning
confidence: 87%
“…In recent years, we have deepened the research on Metasploit's Android payload and found that the payload source code is modifiable, which offers a more targeted and more effective way (List 2) to solve the root cause than other approaches. 17 The code shows that there is a start method in the service startup, which is the core code of the execution payload. 18 Then, if one wishes to achieve a sustainable connection to the load, one needs to know how to obtain the start method of the service and load the running process continuously.…”
Section: The Improvement Of Permeability Stability Under Kalimentioning
confidence: 99%
“…The entity-based researches such as [15][16][17][18] consider the vehicle as the object of the reputation, and they will decide the behavior of vehicular networks by judging the reputation of each vehicle entity.…”
Section: Related Workmentioning
confidence: 99%
“…When a vehicle broadcasts a false message in the Vehicular networks, the vehicles in the same network may take the wrong actions, leading to a bad traffic accident. Herein, to construct a robust and secure trust management framework [15][16][17][18][19][20][21][22][23][24][25][26][27] for the Internet of connected vehicles turns out to be a critical problem for the actual deployment of UGV.…”
Section: Introductionmentioning
confidence: 99%
“…The surveillance application using wireless networks acquires real-time and accurate multimedia information conveniently, and it is widely used in IoTs [10], IoVs [16], and so on. Most of wireless network researches focus on the data transport and management [13,14], the private-preserving [3,4,21] and network attack [12,15], which are also suitable for wireless multimedia surveillance networks.…”
Section: Related Workmentioning
confidence: 99%